Epidemiology of leisure-time physical activity in socio-demographic, lifestyle and psychological characteristics of men and women in Greece: the ATTICA Study - Lentzas Yannis; Panagiotakos Demosthenes B; Pitsavos Christos; Stefanadis Christodoulos (BMC, 2005)
Abstract Background We aimed to evaluate the prevalence, frequency and type of leisure-time physical activity (LTPA) among adults in Greece, as well as its relationship with socio-demographic, lifestyle and clinical characteristics of these people. Methods From May 2001 to December 2002 we randomly enrolled 1514 men and 1528 women, without any evidence of cardiovascular or any other chronic disease. The sampling was stratified by the age - gender distribution of (census 2001) of the greater area of Athens. Weekly energy expenditure assessed by considering frequency, duration (in minutes) and intensity of sports related physical activity during a usual week. Results 53% of men and 48% of women were classified as physically active. Men were more likely to be active as compared to women (p < 0.05), while the lowest activity rates were observed in 40 to 49 years old participants (p < 0.01). Physically active people had higher occupation skills, were more likely to live in rural areas, to be unmarried, non smokers and they were devoted to a healthier dietary pattern, as compared to sedentary, irrespective of age and sex (all p < 0.05). In addition, the cumulative risk factors score of obesity, hypertension, hypercholesterolemia and diabetes, was inversely associated with activity status (p < 0.001). Finally, physically active men and women were less likely to report depressive symptoms (p < 0.01), after various adjustments were made. Conclusion Half of the studied population reported physically inactive, indicating that sedentary lifestyle becomes a serious epidemic in Greece. High occupation skills, non-smoking, devotion to a healthier dietary pattern and a better cardiovascular risk factors profile were some of the determinants of physically active people.